The Effect of Sacha Inchi Leaf Extract (Plukenetia volubilis) with Different Doses on Reducing Uric Acid Levels in Mice (Mus musculus) - Mulyani, Leni Sri; Mulyaningsih, Sri; Alya, Rahma; Taufik, De Budi Irwan (Journal Of Biology Education Research (JBER), 2025)
Sacha inchi (Plukenetia volubilis) is an ancestral plant native to the Amazon rainforest that has been adopted as a food source due to its high nutritional value, which has gradually been recognized for its potential health benefits for humans. One of its benefits is as a natural agent for lowering uric acid levels, due to its antioxidant content and active compounds such as flavonoids, which function as anti-inflammatory and cell protective agents. Although P. volubilis seeds have been extensively studied, the potential of its leaves as an alternative treatment for hyperuricemia remains largely unexplored. This study aims to determine the effect of sacha inchi (P. volubilis) leaf extract at different doses 0.35 mL/mouse, 0.40 mL/mouse, and 0.45 mL/mouse on reducing uric acid levels in mice (Mus musculus) and to identify the most effective dose for reducing uric acid levels in mice. This study used 24 male mice aged 3–4 months with a body weight not exceeding 25 g. The study design used a Randomized Block Design (RBD) with four treatments and six replicates. The treatments consisted of control (without extract), doses of 0.35 mL, 0.40 mL, and 0.45 mL of P. volubilis leaf extract. The P. volubilis leaf extract was administered orally via a mouth tube. The extract was obtained from the leaves of the P. volubilis using the maceration method. The mice were first induced with hyperuricemia using 1 mL of chicken liver juice per mouse. Uric acid levels were measured before and after treatment using a GCU test strip. Data were analyzed using a one way ANOVA test followed by a Duncan test at a significance level of 5%. The results showed significant differences between treatments (p = 0.001 < 0.05). The 0.45 mL dose was the most effective in lowering uric acid levels, from an average of 4.7 mg/dL to 3.4 mg/dL, and was significantly different from other doses based on Duncan's test. This study concluded that sacha inchi leaf extract has the potential to be used as a natural alternative for lowering blood uric acid levels.